Khan River and Bear Lake: Two Natural Titanite Reference Materials for High‐Spatial Resolution U‐Pb Microanalysis. Issue 4 (10th August 2022) - Mazoz, Ariela; Gonçalves, Guilherme O.; Lana, Cristiano; Buick, Ian S.; Corfu, Fernando; Kamo, Sandra L.; Wang, Hao; Yang, Yue‐Heng; Scholz, Ricardo; Queiroga, Gláucia; Fu, Bin; Martins, Lorena; et al.
Abstract : The Khan River (Namibia) and Bear Lake (Canada) titanites are investigated as potential reference materials (RM) for LA‐ICP‐MS applications. The Bear Lake titanite is texturally and compositionally homogeneous. The Khan River titanite is texturally heterogeneous and characterised by variable trace element compositions and total rare earth element contents. However, both titanites have consistent U‐Pb and Nd‐isotope ratios. U‐Pb isotope dilution‐thermal ionisation mass spectrometry analyses yielded Pbc ‐uncorrected intercept ages of 516.3 ± 1.3 Ma (2 s, n  = 5, MSWD = 2.4) and 1067.81 ± 0.74 Ma (2 s, n  = 4, MSWD = 0.35) for Khan River and Bear Lake titanites, respectively. Multiple U‐Pb LA‐SF/MC‐ICP‐MS analyses gave consistent Pbc ‐uncorrected intercept ages for both, Khan River (517 ± 1/5 Ma, 2 s, n  = 262, MSWD = 1.5) and Bear Lake (1070 ± 1/11 Ma, 2 s, n  = 325, MSWD = 0.88). U‐Pb SHRIMP analyses on the same material returned identical (within uncertainty) ages. Khan River and Bear Lake gave internally consistent solution MC‐ICP‐MS 143 Nd/ 144 Nd ratios of 0.511587 ± 0.000027 (2 s, n  = 2) and 0.512321 ± 0.000004 (2 s, n  = 2), respectively. The 143 Nd/ 144 Nd ratios via solution‐MC‐ICP‐MS and LA‐ICP‐MS all agree within uncertainty and suggest that both titanites can be used as RMs for Nd‐isotope analyses. Key Points: The Bear Lake titanite is texturally and compositionally homogeneous. The Khan River titanite is texturally heterogeneous and characterised by variable trace element compositions. Both titanites have consistent U‐Pb and Nd isotope ratios. Multiple U‐Pb LA‐SF/MC‐ICP‐MS measurements gave consistent Pbc ‐uncorrected intercept ages for the Khan River (517 ± 1/5 Ma) and Bear Lake (1070 ± 1/11 Ma) titanites comparable to existing ID‐TIMS data.